2015
DOI: 10.1038/tpj.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Novel associations between FAAH genetic variants and postoperative central opioid-related adverse effects

Abstract: Opioid effects are potentiated by cannabinoid agonists including anandamide, an endocannabinoid. Inter-individual variability in responses to opioids is a major clinical problem. Multiple deaths and anoxic brain injuries occur every year in due to opioid induced respiratory depression in surgical patients and drug abusers of opioids and cannabinoids. This study aimed to determine specific associations between genetic variants of fatty acid amide hydrolase (FAAH) and postoperative central opioid adverse effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…In our previous prospective genotype-blinded study in 259 white children aged 6-15 years, undergoing tonsillectomy, we reported that FAAH SNPs rs4141964, rs3766246, rs324420, rs2295632 and kgp12517369 increase the odds of PONV by more than twofold, and had nominal associations with RD and prolonged postanesthesia care unit stay [17]. The first four SNPs listed above are also associated with HCVR in the present study, providing further validation.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In our previous prospective genotype-blinded study in 259 white children aged 6-15 years, undergoing tonsillectomy, we reported that FAAH SNPs rs4141964, rs3766246, rs324420, rs2295632 and kgp12517369 increase the odds of PONV by more than twofold, and had nominal associations with RD and prolonged postanesthesia care unit stay [17]. The first four SNPs listed above are also associated with HCVR in the present study, providing further validation.…”
Section: Discussionsupporting
confidence: 51%
“…Hence, in patients receiving opioids like morphine, factors that increase anandamide levels, or decrease its hydrolysis would be expected to potentiate opioid effects, as would be expected with FAAH variants with reduced function affecting anandamide hydrolysis. We recently reported associations of FAAH variants with RD after outpatient tonsillectomy surgery [17]; in this study, we postulate that use of a sensitive measure of subclinical RD such as HCVR, would allow improved identification of FAAH genetic effects on opioid-related RD before they manifest clinically. To our knowledge, this has not been studied before.…”
mentioning
confidence: 99%
“…Research Article Balyan, Zhang, Chidambaran et al our group, we reported that variants in certain genes in the morphine response pathway, namely, μ-opioid receptor (OPRM1), ATP-binding cassette ABCB1 and FAAH, affect morphine clinical outcomes including RD in children [6][7][8]. The efflux of morphine glucuronides from the hepatic cell is an ATP-dependent process mediated by the ATP-binding cassette transporters including ABCC3 [9,10].…”
Section: Future Science Groupmentioning
confidence: 99%
“…Clinical RD was defined as a persistent (longer than 1 min) oxygen desaturation less than 90% or a respiratory rate less than eight breaths per minute or oxygen desaturation less than 94% in addition to respiratory rate less than ten per minute requiring supplemental oxygen to maintain SpO2 more than 94% in the absence of clinically obvious upper airway obstruction [16]. PONV is defined as occurrence of emesis or requirement of antiemetic administration due to self-reported experience of nausea.…”
Section: Clinical Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation